Римське суспільство і superstitio доби принципату - Петречко, О.М. (My University, 2011)
Петречко О. М. Римское общество и superstitio эпохи принципата В статье рассматривается содержание термина superstitio в эпоху принципата. Впасть в superstitio можно было вследствие чрезмерного соблюдения обрядов. Признаком superstitio было вегетарианство. Разные формы магии, как и астрология, также были проявлениями superstitio. Установлено, что римское общество было суеверным. Суеверия были свойственны всем его слоям. Едва ли не основным признаком δεισιδαιμονία Плутарх называет страх. Принимая во внимание страх, как характерную черту superstitio, мы можем более полно понять отношение римлян к иудаизму и христианству. Содержание терминов superstitio и δεισιδαιμονία изменялось. Но в эпоху принципата римляне понимают их в основном как «извращенную» религию и употребляют их в отношении к чужеземным верованиям, преимущественно восточного происхождения, особенно к иудаизму и христианству. O. Petrechko. Roman society and Superstitio under the Principate This article considers the development and importance of superstitio under the Principate. Strict adherence to forms of worship might have fallen into superstitio. Vegetarianism was a sign of superstitio. Additionally, various forms of magic as well as astrology were manifestation of superstitio. Indeed, it has been well-established that the Roman society was superstitious. Superstitiones were common for all strata of the Roman society. Plutarch nominates fear as almost basic sign of δεισιδαιμονία. Whereas the fear as a characteristic of superstitio, we can fuller understand Romans’ treatment of Judaism and Christianity. The meaning of superstitio and δεισιδαιμονία had been evolving over time. But under the Principate, the Romans regarded them generally as perverted religion and applied them in re alien religious beliefs, par excellence easterlies, especially against Judaism and Christianity.
Keywords: римское общество; принципат; суеверие; суеверный; извращенная религия; Roman society; Рrincipate; superstition; superstitious; perverted religion